Experimental Study on the Half Flat Tip Serrated Trailing Edge for Stand Fan - LEE, Hsiao Mun; LIM, Kian Meng; XIE, Jinlong; LEE, Heow Pueh (Archives of Acoustics, 2020)
The effectiveness of half flat tip serrations on reducing fan blade trailing edge noise was investigated using experimental methods. The experiments were conducted at an anechoic chamber under different rotating fan speeds. Numerical simulations were performed to investigate the mass flow rate generated by the serrated fan and compared with that by the baseline fan. The experimental results showed that the overall amount of noise reduction decreased with the increasing of the distance away from the fan. It was found that the effectiveness of the serrations was not proportional with the rotating speed of the fan where it was most effective at 263 rpm and 2041 rpm with noise reductions about 3.1 dBA and 3.5 dBA, respectively. This phenomenon might be depended on how trailing edge vortex would interact with the serrations at different speeds of the fan. The reduction of mass flow rate reduced with the increasing of the rotating speed and the highest reduction was found at 263 rpm which was about 18% and this reduction was accompanied by overall noise reduction of 3.1 dBA.